2010
DOI: 10.1177/1077801209359193
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Youth Exposed to Domestic Violence: Decentering DV and the Primacy of Gender Stereotypes

Abstract: Up to 8 million American children witness domestic violence (DV) every year. Since this discovery in the mid-1980s, psychologists and social service professionals have conducted research with children exposed to DV. This ethnographic study expands on existing research by examining how youth exposed to DV perceive their experiences and staff interventions. Findings show they draw on gender stereotypes for behaviors, and these frequently resist DV education and the advocates' suggestions for coping. Findings als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
16
1
1
Order By: Relevance
“…Gender also plays a role in how exposure to violence affects subsequent behavior. Studies have shown that youths who witness violence behave in gender-typical ways [43] where males are more likely than females to justify violent behaviors [44]. However, previous research has also shown that females tend to be more negatively affected by changes in the parent-child relationship than males [45].…”
Section: The Role Of Gender and Place On Parental Maltreatmentmentioning
confidence: 99%
“…Gender also plays a role in how exposure to violence affects subsequent behavior. Studies have shown that youths who witness violence behave in gender-typical ways [43] where males are more likely than females to justify violent behaviors [44]. However, previous research has also shown that females tend to be more negatively affected by changes in the parent-child relationship than males [45].…”
Section: The Role Of Gender and Place On Parental Maltreatmentmentioning
confidence: 99%
“…193). Phillips and Phillips (2010) also discuss gender and DVA and observe that the DVA advocates they interviewed: " . .…”
Section: Resultsmentioning
confidence: 99%
“…Sex differences have been studied and documented for many health problems, including heart disease (Azad, Kathiravelu, Minoosepeher, Hebert, & Fergusson, 2011;Claassen, Sybrandy, Appelman, & Asselbergs, 2012;Lawton, 2011), hypertension (Beigh & Jain, 2012;Mounier-Vehier et al, 2012), diabetes (Sekerija et al, 2012), autoimmune disease (Oertelt-Prigione, 2012;Quintero, Amador-Patarroyo, Montoya-Ortiz, Rojas-Villarraga, & Anaya, 2012) and Alzheimer's disease (Sinforiani et al, 2010). The majority of studies of gender roles and norms and their impact on specific health conditions have been generally limited to reproductive health, domestic violence and mental health (Boileau et al, 2008;Collins, von Unger, & Armbrister, 2008;Ghanotakis, Peacock, & Wilcher, 2012;Kerrigan, Andrrinopoulos, Chung, Glass, & Ellen, 2008;Mantell et al, 2009;Paek, Lee, Salmon, & Witte, 2008;Phillips & Phillips, 2010;Wagner, Yates, & Walcott, 2012;Zuo et al, 2012). Less is known about the impact of gender on health behaviors, specifically in the area of obesity and lifestyle factors that influence healthy weight, such as diet (Costanzo, Musante, Friedman, Kern, & Tomlinson, 1999;Fagerli & Wandel, 1999;Frank et al, 2009;Gavin, Fox, & Grandy, 2011;Gray, Cinciripini, & Cinciripini, 1995) and physical activity (Butt, Weinberg, Breckon, & Claytor, 2011;Frank et al, 2009;Gavin et al, 2011;Langer et al, 2009;McLaren, Godley, & MacNairn, 2009;Sjogren, Hansson, & Stjernberg, 2011;…”
Section: Sex Gender and Healthmentioning
confidence: 96%